HIGH-RISK SEXUAL BEHAVIOURS AMONG VULNERABLE WOMEN IN NORTHERN UGANDA, BASELINE RESULTS FROM PE ATYE KENA COHORT STUDY - Francesco Vladimiro Segala; Giulia Micheli; Cristina Seguiti; Andrea Pierantozzi; Robert Lukwiya; Benson Odong; Francesco Aloi; Emmanuel Ochola; Roberto Cauda; Katleen De gaetano Donati; Antonella Cingolani (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objectives: HIV infection among vulnerable women (VW) has been attributed to unfavourable power relations and limited access to sexual and reproductive health information and services. Aim of this work is to report sexually-transmitted infections (STI) prevalence and to assess the impact of HIV awareness, demographic and socio-behavioural factors in a rural area of northern Uganda.